Spiritual and Corporeal Nature of Body in Drama “The Seagull” of Anton P. Chekhov - Waligorska-Olejniczak, Beata (My University, 2011)
The paper focuses on the interpretation of gestures in the drama "The Seagull" perceived as the specific Chekhovian language which sometimes turns out to be more meaningful than the verbal sphere of his plays. We analyse behavioural sphere of the characters in relation to the concept of spiritual nature of the body described by Alexander Lowen. We come to the conclusion that economical kinetics in Chekhov's plays constitutes one of the features which allows the poetics of the Russian playwright to be described as the poetics of negation, poetics of denying. It seems that the most adequate metaphor of the Chekhovian gesture could be the Lotman's notion of "meaningful absence" emphasizing the potential of the work which cannot reach its highest level, the stimulus for the deepened analysis of the text.
Keywords: Great Theatre Reform; Seagull; Wielka Reforma Teatralna; Mewa; Chekhov; Czechow; Aleksander Lowen; Russian Theatre; Yuri Lotman; Jurij Łotman